2022
DOI: 10.3389/fbioe.2021.797359
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Mesenchymal Stem Cell-Derived Exosomes as Drug Delivery Vehicles

Abstract: Exosomes are tiny vesicles with a double membrane structure that cells produce. They range in diameter from 40 to 150 nm and may contain a variety of biomolecules including proteins and nucleic acids. Exosomes have low toxicity, low immunogenicity, and the ability to encapsulate a wide variety of substances, making them attractive drug delivery vehicles. MSCs secrete large amounts of exosomes and hence serve as an excellent source of exosomes. MSCs-derived exosomes have regenerative and tissue repair functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 89 publications
0
41
0
Order By: Relevance
“…Additionally, it has to be noted that the biological capability of MSCs dramatically decreases in age-related disorders [ 33 ], as well in relation with the age of the donors [ 34 ]. Among cell-free approached, stem cell-derived exosomes are gaining popularity in regenerative medicine [ 35 , 36 , 37 ]. Indeed, previous investigations revealed therapeutic potential of stem cell-derived exosomes in numerous disorders such as myocardial ischemia/reperfusion injury, liver/renal failure, and traumatic brain/spinal cord injury [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has to be noted that the biological capability of MSCs dramatically decreases in age-related disorders [ 33 ], as well in relation with the age of the donors [ 34 ]. Among cell-free approached, stem cell-derived exosomes are gaining popularity in regenerative medicine [ 35 , 36 , 37 ]. Indeed, previous investigations revealed therapeutic potential of stem cell-derived exosomes in numerous disorders such as myocardial ischemia/reperfusion injury, liver/renal failure, and traumatic brain/spinal cord injury [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular vesicles (EVs) of MSCs contain microRNA let-7a-5p, which helps reduce apoptosis and enhance autophagy in kidney repair [ 97 ]. Therefore, with the in-depth study of such secretions with membrane structures, cell-based therapeutic research has gradually shifted to non-cellular active substances [ 98 ]. Studies have shown that mesenchymal stem cell-derived exosomes are safe and effective, and especially have significant advantages in reducing the tumorigenicity of cell administration [ 60 , 61 ].…”
Section: Mechanism Of Stem Cells To Repair Endometrial Damagementioning
confidence: 99%
“…Surrounded by lipid bilayers, EdSC can regulate cell–cell communication by transferring a lot of functional biomolecules to recipient cells ( Tran et al, 2020 ; An et al, 2021 ; Arishe et al, 2021 ). As the main paracrine factors of stem cells, many studies established that EdSCs are also involved in the immune response ( Hodge et al, 2021 ; Dai et al, 2022 ), cancer prevention and treatment ( Jiang et al, 2022 ; Nik Nabil et al, 2022 ), antigen presentation ( You et al, 2021 ; Zheng et al, 2022 ), angiogenesis ( Yang et al, 2021 ), drug delivery ( Riau et al, 2019 ; Ding et al, 2022 ; Rao et al, 2022 ), and inflammation ( Shen et al, 2021 ). Multiple pharmacological effects make EdSC attract much attention in enhancing skin wound healing ( Las Heras et al, 2020 ; Al Gailani et al, 2022 ; Dong et al, 2022 ; Opoku-Damoah et al, 2022 ).…”
Section: Recent Emerging Novel Tool: Exosome Derived From Stem Cellmentioning
confidence: 99%